Impact of Media on the Health Consciousness of the Millennial Generation - Singh, Saumya; Kapoor, Pooja; Srivastava, Sanjay; Prakash, Anand (Prabandhan: Indian Journal of Management, 2021)
India, in coming times, is said to be crowned as the youngest country in the world with the highest percentage (64%) of its population as the working population, the maximum of which will be accounted for by the millennials. Wellbeing is a continuous effort cycle, requiring small steps at each stage of life. In this context, this article tried to understand the health consciousness in terms of attitudinal responses among the millennial generation (born after 1990) and the influence of market and media. The paper further explored the role of select media in creating awareness of the healthfulness of products and the health consciousness of college millennials/youth in Delhi NCR. The sample size of 363 respondents consisted of youth ranging from 18 – 25 years of age studying in various colleges of the University of Delhi and its satellite towns like Faridabad, Noida, and Gurgaon. A random stratified sampling method was used to collect the data from the population. Cronbach’s alpha test was applied for checking the validity and reliability. Using a 5 - point Likert scale, and with the help of variables, namely age, gender, socioeconomic status, and health consciousness, it was observed that the health consciousness of the millennial generation was primarily affected by the media (particularly social media). Moreover, too much exposure to the media altered the behavior of the millenials.